Activity of caffeic acid phenethyl ester in Caenorhabditis elegans. (November 2016) - Coleman, Jeffrey J; Komura, Tomomi; Munro, Julia; Wu, Michael P; Busanelli, Rakhee R; Koehler, Angela N; Thomas, Méryl; Wagner, Florence F; Holson, Edward B; Mylonakis, Eleftherios
Aim: Caffeic acid (3, 4-dihydroxycinnamic acid) phenethyl ester (CAPE), the major constituent of propolis, is able to increase the survival of the nematode Caenorhabditis elegans after infection with the fungal pathogen Candida albicans .Results: CAPE increases the expression of several antimicrobial proteins involved in the immune response to C. albicans . Structural derivatives of CAPE were synthesized to identify structure–activity relationships and decrease metabolic liability, ultimately leading to a compound that has similar efficacy, but increased in vivo stability. The CED-10(Rac-1)/PAK1 pathway was essential for immunomodulation by CAPE and was a critical component involved in the immune response to fungal pathogens.Conclusion: Caenorhabditis elegans is an efficient heterologous host to evaluate immunomodulatory compounds and identify components of the pathway(s) involved in the mode of action of compounds.